The impacts of evaluation duration and product types on review extremity. Issue 5 (9th September 2019) - Zhu, Huawei; Tu, Rungting; Feng, Wenting; Xu, Jiaojiao
Abstract : Purpose: Extreme online reviews can have great impacts on consumers' purchase decisions. The purpose of this paper is to investigate when users are more likely to provide extreme ratings. The study draws inference from attitude certainty theory and proposes that review extremity is influenced by the interaction of evaluation duration and product/service types: for hedonic products/services, shorter evaluation duration can foster attitude certainty, leading to higher review extremity; in contrast, for utilitarian products/services, longer evaluation duration can increase attitude certainty, resulting in more extreme reviews. Design/methodology/approach: Three studies were conducted to test the hypotheses: Study 1 is an empirical analysis of 3, 000 reviews from an online retailing website; Studies 2 and 3 are two between-subject experiments. Findings: Results from three studies confirm the hypotheses. Study 1 provides preliminary evidence on how review extremity varies in evaluations of different durations and product/service types. Results from Studies 2 and 3 show that for hedonic products/services, the shorter the evaluation duration, the more likely users are to give extreme ratings; however, for utilitarian products/service, the longer the evaluation duration, the more likely users are to give extreme reviews; and attitude certainty plays a mediating role between evaluation duration and review extremity. Originality/value: Findings from this study provide understandings on when a fast rather than a slow evaluation can lead to more extreme reviews. The results also highlight the role of users' attitude certainty in the underlying mechanism.